(No^ERKI O {OPENE(B.s (NMANOGRAFIQs - (Nq(B. (Ni(B. (NmILX[TEJNs ((NmOSKWAs (NmUZYKAs, 1987)
(NqKOW iSAKOWI^ mILX[TEJN (B- (NODIN IZ PREDSTAWITELEJ ZWME^ITELXNOJ ILEQDY PIANISTOW (B- (NPEDAGOGOW(B, (NS DEQTELXNOSTX@ KOTOROJ SWQZANO MO]NOE WOSHOVDENIE SOWETSKOJ PIANISTI^ESKOJ [KOLY(B.s
Keywords: (NMONOGRAFIQs